The effect of Aloe vera on reducing episiotomy pain and improving wound healing: A systematic review and meta-analysis - Hadis Shahrahmani; Giti Ozgoli; Fatemeh Bayat; Maryam Amighi; Fatemeh Abdi; Nourossadat Kariman (Mashhad University of Medical Sciences, 2021)
Introduction: Episiotomy is one of the causes that can affect mothers' postpartum quality of life. Aloe Vera plant has been suggested as one of the ways to heal wounds and reduce pain. Regarding to these properties, several clinical trial studies have been conducted to determine the effect of aloe vera on episiotomy pain relief and wound healing, and different findings have been reported. This study was performed with aim to determine the effect of Aloe Vera on episiotomy pain relief and wound healing. Methods: In this systematic review study, the databases of Scopus, PubMed (MEDLINE), Embase, Proquest, Cochrane Central Register of Controlled Trials (CENTRAL), Cochrane Library and Web of Science were searched using the keywords of "pain", "Wound", "Healing", "Episiotomy", " Perineum" and "Aleo Vera" by OR and AND without time, language and geographical limitation until 23 April 2021. The quality of the articles was evaluated using the Cochran Group tool and data were analyzed by Stata software (version 14). Cochran test and I2 index were used to assess the heterogeneity of the articles. Results: Finally, 9 articles with sample size of 611 people were included in this systematic review study. Preliminary studies showed the effectiveness of Aloe Vera in wound healing and pain relief. Four studies with sample size of 258 patients had the potential to perform the meta-analysis for pain outcome. Results of the meta-analysis showed that Aloe vera can reduce pain intensity compared to the control group (P<0.05). Conclusion: Aloe Vera seems to be effective in repairing episiotomy wounds and reducing pain; however, high quality studies with sufficient sample size are recommended for definitive results.